Estudio de mercado para identificar gustos, preferencias y el posicionamiento de las ópticas en la ciudad de Quevedo - Chávez Macías, Angélica María (2012)
The optics dedicated to ensure eye health of all people who have visual defects, providing optometric service and sales of eyewear and accessories, with financial products, middle and high cost of the lenses as: carey, metal, semi air, and the air full. Through this study we investigated market that level optical foundations are really posesionadas. And the largest optical positioning Optirey Optics is being one of the selling optical frames and mirrors of different prices, quality and providing good service. The overall project aims to expand its high optical positioning and greater market segmentation such as Optical Optirey with senior professionals, so have greater sales and greater profitability increased demand, and lower optical positioning make and implement strategic plans to target new markets Quevedo. It also undertook a questionnaire to each of the optics we took as a reference for the following study, and we were able to realize that in addition to providing Optical Optirey optometric services also provides an additional service that is the eye... that differentiates other optical